O consumo cultural das músicas pop com conteúdos eróticos: constituindo identidades infantis na contemporaneidade - Silva, Clara Beatriz Santos Pereira da (2016)
This work focused on the constitution of child identity, in particular, the eroticization of child identity based on the cultural consumption of pop songs with erotic content and its materialization in a specific kindergarten school from the city of Natal, Brazil. The present study aimed to highlight and discuss how cultural consumption of pop songs with erotic content contributes to the formation of eroticized children's identities, supported by Cultural Studies in Education in a post-structuralism aspect. It is known that childhood has a cultural, social and historical background, subject to changes related to the situations in which children are involved. Accordingly, it is emphasized that the contemporaneity set up unique conditions that produce new ways of being a child and living childhood again. From this statement, it was considered that the pop songs lyrics with erotic content and certain practices related to them, have effects on the ways of being a child in contemporaneity and operate on the constitution of an eroticized child identity. Thus, it sought inspiration in Foucault's discourse analysis contributions to understand the lyrics content and the children’s speeches. As well as methodological strategies, there was an ethnographic inspiration look at the children surveyed in a kindergarten school from the city of Natal, through entries posted in a journal about the children daily activities that were related to the research questions. The analysis focused on the fragments of the pop songs lyrics with erotic content; the children speeches and actions were observed and recorded in the school context that were related to the pop songs with erotic content and some of the cultural framework materials that refer to pop songs with erotic content in circulation nowadays. Therefore, it was possible to show, among other findings, that children of contemporaneity along with the effects of pop songs with erotic content invest in bodily movements that contribute to the construction of a sensual and eroticized body. Also, it is evident that the songs in question demonstrate a morally wrong adult behavior of being a child, marked by conflicts of generations. These aspects contribute in potential for the formation of eroticized children's identities.